Fine-tuning and autoregulation of the intestinal determinant and tumor suppressor homeobox gene CDX2 by alternative splicing - Balbinot, Camille (Cell Death Differ, 2017)
On the basis of phylogenetic analyses, we uncovered a variant of the CDX2 homeobox gene, a major regulator of the development and homeostasis of the gut epithelium, also involved in cancer. This variant, miniCDX2, is generated by alternative splicing coupled to alternative translation initiation, and contains the DNA-binding homeodomain but is devoid of transactivation domain. It is predominantly expressed in crypt cells, whereas the CDX2 protein is present in crypt cells but also in differentiated villous cells. Functional studies revealed a dominant-negative effect exerted by miniCDX2 on the transcriptional activity of CDX2, and conversely similar effects regarding several transcription-independent functions of CDX2. In addition, a regulatory role played by the CDX2 and miniCDX2 homeoproteins on their pre-mRNA splicing is displayed, through interactions with splicing factors. Overexpression of miniCDX2 in the duodenal Brunner glands leads to the expansion of the territory of these glands and ultimately to brunneroma. As a whole, this study characterized a new and original variant of the CDX2 homeobox gene. The production of this variant represents not only a novel level of regulation of this gene, but also a novel way to fine-tune its biological activity through the versatile functions exerted by the truncated variant compared to the full-length homeoprotein. This study highlights the relevance of generating protein diversity through alternative splicing in the gut and its diseases.